The Impacts of Tanjung Sakti Agrotourism on Environmental Conservation in Sindang Panjang Village Lahat Regency - Ade Anugra Utami; Shomedran Shomedran (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2023)
This study aims to determine the impact of Agrotourism on environmental preservation in Sindang Panjang Village. This study uses a descriptive type of research with a qualitative approach. Collecting data using interview, observation, and documentation methods. The subjects of this research are agro-tourism managers, the government of Sindang Panjang Village, and the people of Sindang Panjang Village. The indicators of the research results obtained are; 1) The negative impact of Agrotourism is dependence on tourism and the seasonal nature of tourism. 2) The positive impact of Tanjung Sakti Agrotourism is to preserve, maintain, and use natural resources wisely. The conclusion is that agro-tourism can improve people's living standards and reforest nature.